Teacher Talent Identification Scale (ITP): Evidence of Validity and Accuracy - Tonete Suárez, Janete (2019)
Teacher perceptions have proven to be an important resource in face of the scarcity of validated instruments for identifying talented students in the regular classroom. Therefore, the purpose of this study was to investigate the validity and accuracy of the Talent Identification Scale by the Professor (ITP). The participants were 4 psychologists of the psychological evaluation area (F3), 10 female teachers (F10) and 120 students (F62) aged 9 to 11 years. The ITP has 30 items evaluating the areas of verbal comprehension, spatial reasoning, logical thinking, quick thinking, visual memory and creative thinking. The results indicated evidence of the validity of the internal structure of the ITP by agreement of judges and by the Cohen Kappa coefficient (K = 0.82). Evidence of validity by external criterion was confirmed by comparing the ITP’s total Cognitive Index with another validated test of general intelligence, Nonverbal Testing of Infantile Reasoning (TNVRI) (r=0.30). The ITP areas that contributed most significantly to this validity were visual memory (r=0.37) and creative thinking (r=0.33). The accuracy of the ITP found by the Alpha Coefficient was high (α=0.80). It is concluded that the ITP scale is a valid and precise instrument and can help in the process of identification of talents by professors for meeting the minimum scientific requirements postulated.